fMRI Analysis on Electroacupuncture on Tongli Acupoint in Healthy People - Lin LU; Wanzhang YANG; Yunhai QIU; Liping YE; Linling LI (康复学报)
Objective:To investigate the effect and mechanism of electroacupuncture on Tongli acupoint on the right hand of normal subjects that may activate brain language area by functional magnetic resonance imaging (fMRI).Methods:Twenty-four healthy volunteers were recruited and divided into treatment group and control group. The subjects of the treatment group were stimulated by the electroacupuncture on Tongli acupoint of the right hand, while the subjecs of the control group were stimulated on a fake acupoint beside Tongli with one week time interval and block design scheme. The data were analyzed by SPM8 to generate the image of active brain area. The distribution, voxel and intensity of active areas were compared between the two groups.Results:The active brain area images of both groups include vision, language and cognition areas, such as bilateral calcarine, cerebellum, fusiform, lingual, occipital, precentral gyrus, supplementary motor area, left gyrus frontalis inferior, right gyrus temporalis inferior, etc. There were some overlap of the active areas between the two groups, but the intensities of the active brain areas in the treatment group were higher than the control group. During the first electroacupuncture task, the higher intensities of the treatment group included left cingulum post, posterior central gyrus, precentral gyrus, right middle frontal gyrus, and dorsolateral superior frontal gyrus (P<0.01).In the second task, the areas, including bilateral loran shell, left insula, middle occipital gyrus, superior temporal gyrus, right cingulum post, and gyrus frontalis inferior, had higher intensities in the treatment group than the control group (P<0.01).Conclusion:Language expression might connect with various neural networks which were related to brain regions. The right hemisphere was participated to produce the normal language. Results showed that the bilateral language areas, including BA45 area and cingulum post, were activated when the Tongli acupoint on the right hand was stimulated by electroacupuncture. This study suggested that the electroacupuncture of Tongli acupoint could be the potential strategy to evaluate the clinical efficacy.